Penegakan Hukum Tindak Pidana Cybercrime Berdasarkan Undang-Undang ITE di Polres Empat Lawang - Abdu Rozan Anugerah Pratama; Agus Ariadi (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2026)
The development of information and communication technology has significantly contributed to the increase of digital-based crimes or cybercrime in Indonesia. cybercrime has evolved into various forms, including online fraud, personal data theft, hacking, dissemination of false information, and misuse of electronic media that cause losses to society. This research aims to determine the effectiveness of law enforcement against cybercrime from the perspective of the Electronic Information and Transactions Law within the jurisdiction of Empat Lawang Regional Police, South Sumatra Province, and to analyze the inhibiting factors in its enforcement. This study employed an empirical normative juridical method with a qualitative approach through literature study, interviews, and documentation. The results indicate that law enforcement against cybercrime has been implemented based on the provisions of Law Number 11 of 2008 in conjunction with Law Number 19 of 2016 concerning Electronic Information and Transactions. However, the effectiveness of law enforcement still faces several obstacles, including limited human resources, inadequate digital forensic facilities, difficulties in electronic evidence procedures, and low levels of public digital literacy. The findings imply the importance of strengthening the capacity of law enforcement officers, improving information technology facilities, and enhancing public legal awareness to support effective cybercrime law enforcement in Indonesia.